The Challenges and Strategic Recommendations for Student Services in Higher Education in Cambodia - Moeurn, Chantrea (Educative: Jurnal Ilmiah Pendidikan, 2025)
In alignment with the Royal Government of Cambodia's Vision 2050 and response to Industry 4.0 demands, the Ministry of Education, Youth and Sports has initiated higher education reforms to build human capital. Despite the rapid increase in higher education institutions, from 1 in 1979 to 189 by 2022–2023, student services remain underdeveloped and inadequately supported. This qualitative study explores key challenges in implementing student services across Cambodian HEIs and examines strategic recommendations to improve support systems. Using purposive sampling, 67 participants from seven stakeholder groups were interviewed through semi-structured, one-on-one, and focus group discussions. Thematic analysis identified challenges such as assessment and attention mechanisms, structured and action plans, human and digital infrastructure, physical infrastructure and facilities, budget constraints, and student perspective. To address these issues, the study proposes a strategic and collaborative approach, involving parent ministries, industry and communities, development partners, religion, parents and guardians, and institutional actors. This study offers practical, stakeholder-informed recommendations to enhance student services, which are vital to improving student success, institutional resilience, and the overall quality of higher education in Cambodia.